PVC pipe for communication wiring and its preparation method
Patent Information
- Application Number
- CN202511870639.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-12
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-12-12
AI Technical Summary
[0005]针对现有技术的不足,本发明提供了一种通信布线用PVC管材及其制备方法,解决了现有通信布线用PVC管材在加工过程中润滑体系分散不均、硅油易析出以及管材内壁摩擦系数难以持久降低的问题
[0045]1、本发明通过利用端氨基聚硅氧烷中的活性端氨基与马来酸酐接枝聚乙烯中的酸酐基团在挤出加工过程中发生原位化学反应,形成稳固的化学键合,这种方式将聚硅氧烷长链固定在聚乙烯网络骨架上,在赋予通信布线用PVC管材内壁持久低摩擦系数的同时,解决了传统硅油类润滑剂因与聚氯乙烯树脂相容性差而易迁移至管材表面造成析出、喷霜的缺陷,保证了管材在长期使用过程中的表面清洁度与穿线滑爽性。
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer materials technology, specifically to a PVC pipe for communication cabling and its preparation method. Background Technology
[0002] Polyvinyl chloride (PVC) conduits for communication cabling are widely used in the field of protective sheathing for communication optical cables and electrical cables due to their excellent electrical insulation, flame retardancy, and corrosion resistance. In actual engineering construction, the coefficient of friction of the inner wall of PVC conduits for communication cabling affects the efficiency and length of cable laying. Therefore, the inner wall of the conduit is required to have a durable and extremely low coefficient of surface friction. At the same time, considering the complex environmental stresses faced by the conduit during transportation, underground burial, and long-term service, PVC conduits for communication cabling also need to have excellent impact resistance, ring stiffness, and good dimensional stability to ensure reliable protection for the internal cables.
[0003] However, existing technologies for reducing the friction coefficient of PVC pipes directly add small-molecule external lubricants such as dimethyl silicone oil, paraffin wax, or stearic acid. Because these free lubricant molecules have a physical mixing relationship with the PVC resin matrix and have large polarity differences, their compatibility is limited. During long-term storage or use of the pipes, the free lubricant molecules are prone to migrate to the surface, resulting in whitening, blooming, or oily exudates on the pipe surface. This not only affects the appearance quality of the pipes and the interfacial adhesion performance of subsequent connections, but also causes the lubrication layer on the inner wall of the pipes to gradually disappear, causing the friction coefficient to increase over time, which cannot meet the requirements of long-distance wiring construction for durable lubrication.
[0004] Furthermore, rigid PVC materials inherently suffer from low notched impact strength and poor toughness. Although existing technologies use inorganic powders such as calcium carbonate to reduce costs and improve rigidity, the untreated inorganic particles have weak interfacial bonding with the organic resin matrix, easily agglomerating in the matrix and forming stress concentration points, which in turn leads to brittleness and decreased impact resistance of the pipe. Therefore, this invention proposes a PVC pipe for communication cabling and its preparation method to overcome the shortcomings of existing technologies. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a PVC pipe for communication cabling and its preparation method, which solves the problems of uneven distribution of the lubrication system, easy precipitation of silicone oil, and difficulty in persistently reducing the friction coefficient of the inner wall of the pipe in the processing of existing PVC pipes for communication cabling.
[0006] To achieve the above objectives, the present invention provides the following technical solution: a PVC conduit for communication cabling, wherein the PVC conduit for communication cabling is made from raw materials comprising the following parts by weight: 90.0-110.0 parts of polyvinyl chloride resin; 3.5-4.5 parts of calcium-zinc composite heat stabilizer; 0.3-0.4 parts of stearic acid; 0.4-0.5 parts of polyethylene wax; 3.0-5.0 parts of maleic anhydride-grafted polyethylene; 1.0-2.0 parts of acrylate processing aid; 10.0-15.0 parts of nano-calcium carbonate; and 1.4-2.8 parts of active lubricant precursor.
[0007] By adopting the above technical solution, an in-situ reactive lubrication enhancement system is constructed using maleic anhydride-grafted polyethylene and an active lubricating precursor, thus achieving a balance between the slip properties and mechanical properties of the inner wall. The specific mechanism of action is as follows:
[0008] Physical swelling and dispersion mechanism: The active lubricating precursor is formed by pre-swelling zinc stearate in amino-terminated polysiloxane at high temperature. As a rigid metal soap molecule, zinc stearate is physically wrapped and swollen by the flexible amino-terminated polysiloxane long-chain molecules, which destroys the original tight crystal stacking structure of zinc stearate. When the active lubricating precursor enters the polyvinyl chloride matrix, the amino-terminated polysiloxane carries zinc stearate molecules to rapidly penetrate into the gaps between polyvinyl chloride resin particles at the molecular or micro-nano scale, avoiding local agglomeration of zinc stearate and improving the internal and external lubrication balance efficiency in the initial melting process.
[0009] Chemical anchoring lubrication mechanism: Under the high temperature and high shear of pipe forming, the anhydride groups on the maleic anhydride-grafted polyethylene molecular chain have high reactivity, while the terminal amino polysiloxane in the active lubricating precursor has active terminal amino groups. The terminal amino groups nucleophilically attack the anhydride ring, undergoing amidation or imidization reactions to form covalent chemical bonds (imide bonds or amide bonds). This reaction anchors the originally free polysiloxane long chain to the polyethylene backbone.
[0010] Synergistic effect of compatibility and toughening: The polyethylene backbone of maleic anhydride-grafted polyethylene has good compatibility with polyvinyl chloride resin and polyethylene wax, forming a physically entangled network. The anchored polysiloxane long chains extend at the matrix interface, which not only reduces the friction coefficient of the pipe through the low surface energy characteristics of silicon-oxygen bonds, but also solves the problem of blooming or precipitation caused by the easy migration of traditional silicone oil lubricants to the surface due to the chemical fixation at one end, thus ensuring the long-term surface smoothness of the pipe. At the same time, nano-calcium carbonate is dispersed in situ in the toughening phase, which plays a synergistic role in enhancing toughness.
[0011] Preferably, the active lubricating precursor is a mixture obtained by swelling and compounding of terminal amino polysiloxane and zinc stearate under heating conditions, wherein the weight ratio of terminal amino polysiloxane to zinc stearate is (2.0-3.0):1.
[0012] By adopting the above technical solution, the weight ratio of aminopolysiloxane to zinc stearate is controlled at (2.0-3.0):1, which ensures that zinc stearate reaches a saturated swelling state at high temperature without phase separation. If the proportion of zinc stearate is too high, zinc stearate will recrystallize and precipitate after cooling, which will destroy the homogeneity of the precursor. If the proportion of zinc stearate is too low, it cannot provide sufficient initial thermal stability and demolding lubrication. The metastable composite formed by this ratio exhibits the best rheological modification effect in subsequent extrusion processing.
[0013] Preferably, the particle size of the nano-calcium carbonate is 40nm-80nm; and the grafting rate of maleic anhydride in the maleic anhydride-grafted polyethylene is 0.8%-1.2%.
[0014] By adopting the above technical solution, 40nm-80nm nano-calcium carbonate has a large specific surface area, which can physically adsorb or weakly chemically interact with the remaining anhydride groups on maleic anhydride-grafted polyethylene to form a core-shell flexible interface layer, thereby improving the notched impact strength of the pipe. The maleic anhydride grafting rate is controlled at 0.8%-1.2%, which ensures that there are sufficient anhydride groups to anchor the terminal amino polysiloxane, while avoiding the problem of decreased processing fluidity caused by excessive cross-linking of molecular chains or excessive polarity due to excessive grafting rate.
[0015] Preferably, the amino value of the terminal amino polysiloxane is 0.3 mmol / g-0.6 mmol / g, and the viscosity of the terminal amino polysiloxane at 25°C is 1000 mPa·s-5000 mPa·s.
[0016] By adopting the above technical solution, an amino value in the range of 0.3 mmol / g-0.6 mmol / g provides a moderate density of reactive sites. Too few reactive sites will result in weak anchoring and the silicone oil will still have the risk of migration; too many reactive sites will lead to a sharp increase in the viscosity of the system, forming gel points and affecting the surface smoothness of the pipe. The viscosity range of 1000 mPa·s-5000 mPa·s makes the terminal amino polysiloxane have both good film-forming lubricity and easy dispersion in a high-speed mixer, ensuring that the precursor can be uniformly coated on the surface of polyvinyl chloride resin and nano calcium carbonate.
[0017] Secondly, the present invention provides a method for preparing PVC pipes for communication cabling, using the following technical solution:
[0018] A method for preparing PVC conduit for communication cabling, the method comprising the following steps:
[0019] S1. Preparation of active lubricating precursor: The terminal amino polysiloxane is mixed with the zinc stearate, and the zinc stearate is swollen in the terminal amino polysiloxane under heating and stirring conditions. After cooling, the active lubricating precursor is obtained.
[0020] S2. High-speed mixing: The polyvinyl chloride resin, the calcium-zinc composite heat stabilizer, the stearic acid and the polyethylene wax are put into a high-speed mixer for initial mixing; after heating, the maleic anhydride grafted polyethylene, the acrylate processing aid and the nano calcium carbonate are added; when the temperature is further increased to a specific temperature range, the active lubricating precursor prepared in step S1 is added; after high-speed stirring, the material is discharged.
[0021] S3, Cooling and Mixing: The material obtained in step S2 is cooled in a cold mixer and allowed to stand and mature to obtain a dry PVC mixture;
[0022] S4. Reactive extrusion molding: The PVC dry mixture is added to an extruder, and after plasticizing extrusion, shaping, cooling and cutting, the PVC pipe for communication cabling is obtained.
[0023] By adopting the above technical solution, the process stability and product quality of the system are improved by using a process route that combines stepwise preparation of precursors with segmented feeding and mixing.
[0024] Advantages of the pre-swelling process: In step S1, before extrusion processing, zinc stearate is pre-swelled in the terminal amino polysiloxane in the reactor. This process liquefies the solid lubricant and eliminates the risk of agglomeration of zinc stearate in the dry mix due to electrostatic adsorption.
[0025] Advantages of segmented feeding and temperature control: In step S2, the active lubricating precursor is added only when the material temperature is relatively high (112℃-115℃). This is to use the high temperature to quickly reduce the viscosity of the terminal amino polysiloxane, so that the pores of the polyvinyl chloride resin formed by the terminal amino polysiloxane at this temperature are open and can penetrate into the resin in a short time. At the same time, delaying the addition of the active lubricating precursor avoids the lubricant from prematurely encapsulating the resin particles and affecting the thermal stabilization effect of the calcium zinc composite heat stabilizer on the resin.
[0026] Reactive extrusion control: Step S4 utilizes the shear heat and conduction heat of the extruder to activate the chemical reaction between amino and anhydride groups in the compression and metering sections of the screw, thereby achieving in-situ modification.
[0027] Preferably, in step S1, the heating and stirring temperature is 110℃-120℃, the stirring time is 20min-30min, and the material is discharged after natural cooling to 50℃-60℃ after heating is stopped.
[0028] By adopting the above technical solution, the temperature range of 110℃-120℃ is slightly higher than the softening point of zinc stearate, which intensifies the movement of zinc stearate molecular chain segments, gradually untangling and dissolving in the terminal amino polysiloxane. The isothermal time of 20min-30min ensures the thermodynamic balance of the swelling system. Natural cooling to 50℃-60℃ before discharge can prevent the crystallization of zinc stearate caused by sudden cooling, keeping the precursor in a homogeneous paste or viscous liquid state, which is convenient for subsequent metering and addition.
[0029] Preferably, step S2 is specifically operated as follows: the polyvinyl chloride resin, the calcium-zinc composite heat stabilizer, the stearic acid, and the polyethylene wax are added to the high-speed mixer at a speed of 450 rpm-550 rpm; the high-speed mixer is turned on to utilize frictional heat to raise the temperature, and when the material temperature reaches 80℃-85℃, the maleic anhydride grafted polyethylene, the acrylate processing aid, and the nano-calcium carbonate are added; high-speed stirring continues, and when the material temperature rises to 112℃-115℃, the active lubricating precursor is added; high-speed stirring is continued for 120s-150s, and when the material temperature reaches 120℃-125℃, the material is discharged to the cold mixer.
[0030] By adopting the above technical solution, a gradient dispersion model was established by feeding materials in three stages:
[0031] Phase 1 (room temperature to 80°C): Prioritize contact between small molecule heat stabilizers and external lubricants (stearic acid, polyethylene wax) and the surface of polyvinyl chloride resin to prevent heat degradation of the resin and provide basic fluidity;
[0032] The second stage (80℃ to 112℃): Maleic anhydride-grafted polyethylene and nano-calcium carbonate are added before the resin begins to soften. High shear force is used to break up the nano-agglomerates, and the affinity of maleic anhydride-grafted polyethylene for inorganic powders is used to achieve preliminary coating.
[0033] The third stage (112℃ to 125℃): When the resin micropores are fully opened, add the active lubricating precursor so that the active lubricating precursor is absorbed by the resin. Finally, maintain high-speed stirring for 120s-150s to ensure that all components are uniformly distributed at the microscale, laying the material basis for the subsequent extrusion reaction.
[0034] Preferably, in step S3, the cooling temperature is 40℃-45℃, and the standing ripening time is 12h-24h.
[0035] By adopting the above technical solution, cooling the material to 40℃-45℃ is to prevent material agglomeration and terminate unnecessary side reactions. The 12h-24h static curing process is a key step to eliminate static electricity and balance the density differences between the components of the dry mix. During the curing process, the active lubricating precursor further penetrates into the deep interior of the polyvinyl chloride resin, making the apparent density of the dry mix more uniform, thereby maintaining a constant back pressure when feeding into the extruder and reducing pipe wall thickness fluctuations.
[0036] Preferably, in step S4, the extruder is a conical twin-screw extruder, and the temperature settings for each zone of the conical twin-screw extruder are as follows:
[0037] The feeding section temperature of the conical twin-screw extruder is 150℃-160℃; the compression section temperature is 165℃-175℃; the metering section temperature is 175℃-185℃; the confluence core temperature is 175℃-180℃; and the die temperature is 185℃-190℃.
[0038] The main screw speed of the conical twin-screw extruder is 18 rpm-25 rpm, and the feeding speed is 20 rpm-28 rpm.
[0039] By adopting the above technical solution, the set temperature gradient (from 150℃ to 190℃) not only meets the plasticization requirements of polyvinyl chloride resin, but also matches the activation energy required for the reaction between terminal amino groups and acid anhydride groups.
[0040] Feeding section (150℃-160℃): The lower temperature prevents the material from melting too early at the feed inlet, which could cause bridging, and at the same time, it begins to preheat the material.
[0041] Compression section (165℃-175℃): As the screw channel becomes shallower, the shear force increases and the material melts. At this time, the terminal amino polysiloxane and maleic anhydride grafted polyethylene begin to come into contact and initiate a grafting reaction.
[0042] Combination core (175℃-185℃) and die head mold (185℃-190℃): The high-temperature zone ensures that the chemical reaction is complete, while giving the pipe surface a good gloss.
[0043] Speed matching: The main unit speed of 18rpm-25rpm and the feeding speed of 20rpm-28rpm ensure that the material residence time in the screw is moderate, which allows the reaction to proceed fully and prevents the polyvinyl chloride resin from thermally decomposing and carbonizing.
[0044] This invention provides a PVC conduit for communication cabling and its manufacturing method. It has the following beneficial effects:
[0045] 1. This invention utilizes the in-situ chemical reaction between the active terminal amino groups in the terminal amino polysiloxane and the anhydride groups in the maleic anhydride-grafted polyethylene during the extrusion process to form a stable chemical bond. This method fixes the long chain of polysiloxane onto the polyethylene network skeleton, giving the inner wall of the PVC pipe for communication cabling a durable low coefficient of friction, while solving the defects of traditional silicone oil lubricants that easily migrate to the pipe surface due to poor compatibility with polyvinyl chloride resin, causing precipitation and blooming. This ensures the surface cleanliness and smoothness of the pipe during long-term use.
[0046] 2. This invention improves the interfacial adhesion between inorganic nanoparticles and the organic polyvinyl chloride resin matrix by using maleic anhydride-grafted polyethylene as an interface modifier. The maleic anhydride-grafted polyethylene coats the surface of the nano-calcium carbonate to form a flexible transition layer, which inhibits the aggregation of nanoparticles and promotes the uniform dispersion of nano-calcium carbonate in the matrix to generate a silver shear band toughening mechanism. As a result, the PVC pipe for communication cabling obtains excellent impact resistance and ring stiffness, reducing the risk of brittle fracture during construction, laying and transportation.
[0047] 3. This invention pre-swells zinc stearate in amino-terminated polysiloxane, transforming solid metal soap into a liquid or semi-solid active fluid. This fluid is then added within a specific temperature range when the micropores of the PVC resin particles open. This ensures that the lubricating component can quickly penetrate into the interior of the resin particles rather than simply adsorbing onto the surface. This avoids interference with the thermal stability of the calcium-zinc composite heat stabilizer, resulting in excellent rheological stability of the PVC dry mix. During reactive extrusion, the main machine current fluctuates minimally, and the extruded pipe exhibits uniform wall thickness and good dimensional stability. Detailed Implementation
[0048] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the preparation examples, comparative examples, and test examples. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0049] Preparation Examples 1-3:
[0050] Preparation Example 1:
[0051] 500g of amino-terminated polysiloxane and 200g of zinc stearate were added to a stainless steel reactor equipped with a heating jacket and a mechanical stirrer. The mechanical stirrer was turned on and the speed was set to 400 rpm. At the same time, heat transfer oil was introduced into the heating jacket to raise the temperature of the material in the reactor to 115°C. The temperature was maintained at this temperature and stirred for 25 minutes to allow the zinc stearate to fully swell and partially dissolve in the amino-terminated polysiloxane. Heating was stopped, and stirring was continued to allow the material to cool naturally to 60°C. The resulting milky white paste-like active lubricating precursor was obtained.
[0052] Preparation Example 2:
[0053] 400g of amino-terminated polysiloxane and 200g of zinc stearate were added to a stainless steel reactor equipped with a heating jacket and a mechanical stirrer. The mechanical stirrer was turned on and the speed was set to 350 rpm. At the same time, heat transfer oil was introduced into the heating jacket to raise the temperature of the material in the reactor to 110°C. The temperature was maintained at this temperature and stirred for 20 minutes to allow the zinc stearate to swell in the amino-terminated polysiloxane. Heating was stopped and stirring was continued to allow the material to cool naturally to 50°C. The resulting milky white suspended active lubricant precursor was obtained.
[0054] Preparation Example 3:
[0055] 600g of amino-terminated polysiloxane and 200g of zinc stearate were added to a stainless steel reactor equipped with a heating jacket and a mechanical stirrer. The mechanical stirrer was turned on and the speed was set to 450 rpm. At the same time, heat transfer oil was introduced into the heating jacket to raise the temperature of the material in the reactor to 120°C. The temperature was maintained at this temperature and stirred for 30 minutes to allow the zinc stearate to swell and mix in the amino-terminated polysiloxane. Heating was stopped and stirring was continued to allow the material to cool naturally to 55°C. The resulting milky white, semi-transparent paste-like active lubricant precursor was obtained.
[0056] Examples 1-5:
[0057] Example 1:
[0058] This embodiment provides a method for preparing PVC pipes for communication cabling, including the following steps:
[0059] High-speed mixing: 100.0 parts of polyvinyl chloride resin were added to a high-speed mixer. Under low-speed stirring at 500 rpm, 4.0 parts of calcium-zinc composite heat stabilizer, 0.3 parts of stearic acid and 0.4 parts of polyethylene wax were added. The high-speed mixer was started and the speed was increased to 1500 rpm. The temperature was raised by frictional heat. When the material temperature reached 85°C, 4.0 parts of maleic anhydride grafted polyethylene, 1.5 parts of acrylate processing aid and 12.0 parts of nano calcium carbonate were added. High-speed stirring continued. When the material temperature rose to 115°C, 2.1 parts of the active lubricating precursor obtained in Preparation Example 1 were added. High-speed stirring was continued for 120 seconds. When the material temperature reached 125°C, the material was quickly discharged to a cold mixer.
[0060] Cooling and mixing: The mixture is stirred at low speed in a cold mixer and cooled with cooling water. When the material temperature drops to 40°C, it is discharged and allowed to stand at room temperature for 24 hours to mature, thus obtaining a dry PVC mixture.
[0061] Reactive extrusion molding: The dry PVC mixture is added to a conical twin-screw extruder for extrusion molding. The temperature settings of each zone of the conical twin-screw extruder are as follows: feeding zone temperature is 155℃, compression zone temperature is 170℃, metering zone temperature is 180℃, confluence core temperature is 175℃, die temperature is 185℃, the main screw speed is set to 20 rpm, and the feed speed is set to 22 rpm. The extruded pipe is cooled and shaped in a vacuum sizing box, cooled in a spray water tank, and then traction-cut to obtain the finished pipe.
[0062] Example 2:
[0063] This embodiment provides a method for preparing PVC pipes for communication cabling, including the following steps:
[0064] High-speed mixing: 100.0 parts of polyvinyl chloride resin were added to a high-speed mixer. 4.5 parts of calcium-zinc composite heat stabilizer, 0.3 parts of stearic acid, and 0.4 parts of polyethylene wax were added while stirring at a low speed of 500 rpm. The high-speed mixer was then started and the speed was increased to 1800 rpm to raise the temperature using frictional heat. When the material temperature reached 80°C, 5.0 parts of maleic anhydride-grafted polyethylene, 2.0 parts of acrylate processing aid, and 10.0 parts of nano-calcium carbonate were added. High-speed stirring continued. When the material temperature reached 112°C, 2.8 parts of the active lubricating precursor obtained in Preparation Example 1 were added. High-speed stirring was continued for 150 seconds. When the material temperature reached 120°C, the material was quickly discharged to a cold mixer.
[0065] Cooling and mixing: The mixture is stirred at low speed in a cold mixer and cooled with cooling water. When the material temperature drops to 45°C, it is discharged and allowed to stand and mature at room temperature for 12 hours to obtain a dry PVC mixture.
[0066] Reactive extrusion molding: The dry PVC mixture is added to a conical twin-screw extruder for extrusion molding. The temperature settings of each zone of the conical twin-screw extruder are as follows: feeding zone temperature is 160℃, compression zone temperature is 175℃, metering zone temperature is 185℃, confluence core temperature is 180℃, die temperature is 190℃, the main screw speed is set to 25 rpm, and the feed speed is set to 28 rpm. The extruded pipe is cooled and shaped in a vacuum sizing box, cooled in a spray water tank, and then traction-cut to obtain the finished pipe.
[0067] Example 3:
[0068] This embodiment provides a method for preparing PVC pipes for communication cabling, including the following steps:
[0069] High-speed mixing: 100.0 parts of polyvinyl chloride resin were added to a high-speed mixer. 3.5 parts of calcium-zinc composite heat stabilizer, 0.4 parts of stearic acid, and 0.5 parts of polyethylene wax were added while stirring at a low speed of 500 rpm. The high-speed mixer was then started and the speed was increased to 1500 rpm to raise the temperature using frictional heat. When the material temperature reached 85°C, 3.0 parts of maleic anhydride-grafted polyethylene, 1.0 part of acrylate processing aid, and 15.0 parts of nano-calcium carbonate were added. High-speed stirring continued. When the material temperature reached 115°C, 1.4 parts of the active lubricating precursor obtained in Preparation Example 1 were added. High-speed stirring was continued for 120 seconds. When the material temperature reached 125°C, the material was quickly discharged to a cold mixer.
[0070] Cooling and mixing: The mixture is stirred at low speed in a cold mixer and cooled with cooling water. When the material temperature drops to 40°C, it is discharged and allowed to stand at room temperature for 24 hours to mature, thus obtaining a dry PVC mixture.
[0071] Reactive extrusion molding: The dry PVC mixture is added to a conical twin-screw extruder for extrusion molding. The temperature settings of each zone of the conical twin-screw extruder are as follows: feeding zone temperature is 150℃, compression zone temperature is 165℃, metering zone temperature is 175℃, confluence core temperature is 175℃, die temperature is 185℃, the main screw speed is set to 18 rpm, and the feed speed is set to 20 rpm. The extruded pipe is cooled and shaped in a vacuum sizing box, cooled in a spray water tank, and traction-cut to obtain the finished pipe.
[0072] Example 4:
[0073] This embodiment provides a method for preparing PVC pipes for communication cabling, including the following steps:
[0074] High-speed mixing: 100.0 parts of polyvinyl chloride resin were added to a high-speed mixer. 4.0 parts of calcium-zinc composite heat stabilizer, 0.3 parts of stearic acid, and 0.4 parts of polyethylene wax were added while stirring at a low speed of 500 rpm. The high-speed mixer was then started and the speed was increased to 1500 rpm to utilize frictional heat to raise the temperature. When the material temperature reached 85°C, 4.0 parts of maleic anhydride-grafted polyethylene, 1.5 parts of acrylate processing aids, and 12.0 parts of nano-calcium carbonate were added. High-speed stirring continued. When the material temperature reached 115°C, 1.8 parts of the active lubricating precursor obtained in Preparation Example 2 were added. High-speed stirring was maintained for 120 seconds. When the material temperature reached 125°C, the material was quickly discharged to a cold mixer.
[0075] Cooling and mixing: The mixture is stirred at low speed in a cold mixer and cooled with cooling water. When the material temperature drops to 40°C, it is discharged and allowed to stand at room temperature for 24 hours to mature, thus obtaining a dry PVC mixture.
[0076] Reactive extrusion molding: The dry PVC mixture is added to a conical twin-screw extruder for extrusion molding. The temperature settings of each zone of the conical twin-screw extruder are as follows: feeding zone temperature is 155℃, compression zone temperature is 170℃, metering zone temperature is 180℃, confluence core temperature is 175℃, die temperature is 185℃, the main screw speed is set to 20 rpm, and the feed speed is set to 22 rpm. The extruded pipe is cooled and shaped in a vacuum sizing box, cooled in a spray water tank, and then traction-cut to obtain the finished pipe.
[0077] Example 5:
[0078] This embodiment provides a method for preparing PVC pipes for communication cabling, including the following steps:
[0079] High-speed mixing: 100.0 parts of polyvinyl chloride resin were added to a high-speed mixer. 4.0 parts of calcium-zinc composite heat stabilizer, 0.3 parts of stearic acid, and 0.4 parts of polyethylene wax were added while stirring at a low speed of 500 rpm. The high-speed mixer was then started and the speed was increased to 1500 rpm to raise the temperature using frictional heat. When the material temperature reached 85°C, 4.0 parts of maleic anhydride-grafted polyethylene, 1.5 parts of acrylate processing aid, and 12.0 parts of nano-calcium carbonate were added. High-speed stirring continued. When the material temperature reached 115°C, 2.4 parts of the active lubricating precursor obtained in Preparation Example 3 were added. High-speed stirring was continued for 120 seconds. When the material temperature reached 125°C, the material was quickly discharged to a cold mixer.
[0080] Cooling and mixing: The mixture is stirred at low speed in a cold mixer and cooled with cooling water. When the material temperature drops to 40°C, it is discharged and allowed to stand at room temperature for 24 hours to mature, thus obtaining a dry PVC mixture.
[0081] Reactive extrusion molding: The dry PVC mixture is added to a conical twin-screw extruder for extrusion molding. The temperature settings of each zone of the conical twin-screw extruder are as follows: feeding zone temperature is 155℃, compression zone temperature is 170℃, metering zone temperature is 180℃, confluence core temperature is 175℃, die temperature is 185℃, the main screw speed is set to 20 rpm, and the feed speed is set to 22 rpm. The extruded pipe is cooled and shaped in a vacuum sizing box, cooled in a spray water tank, and then traction-cut to obtain the finished pipe.
[0082] Comparative Examples 1-5:
[0083] Comparative Example 1:
[0084] Compared with Example 1, the difference is that maleic anhydride-grafted polyethylene and the active lubricating precursor of Preparation Example 1 were not added, and the amount of nano-calcium carbonate added was increased to 18.1 parts to make up the total weight parts. The other raw material types, ratios and preparation processes are the same.
[0085] Comparative Example 2:
[0086] Compared with Example 1, the difference is that the active lubricating precursor of Comparative Example 1 is not used. Instead, 1.5 parts of dimethyl silicone oil and 0.6 parts of zinc stearate are directly added to a high-speed mixer. The dimethyl silicone oil does not have reactive amino functional groups. The other raw materials, proportions and preparation processes are the same.
[0087] Comparative Example 3:
[0088] Compared with Example 1, the difference is that zinc stearate was not added when preparing the active lubricating precursor. Only 1.5 parts of terminal amino polysiloxane were directly sprayed into the high-speed mixer. That is, there is no additional zinc stearate in the system for forming ion coordination intermediates. The other raw material types, ratios and preparation processes are the same.
[0089] Comparative Example 4:
[0090] Compared with Example 1, the difference is that the step of preparing the active lubricating precursor was omitted. Instead, 1.5 parts of terminal amino polysiloxane and 0.6 parts of zinc stearate were used as independent components and directly added to the high-speed mixer along with other powder raw materials during the high-speed mixing stage. No preheating swelling complexation treatment was performed. The other raw material types, ratios and preparation processes were the same.
[0091] Comparative Example 5:
[0092] Compared with Example 1, the difference is that 4.0 parts of maleic anhydride-grafted polyethylene are replaced with 4.0 parts of low-density polyethylene resin without anhydride groups, so that the system cannot undergo amidation grafting reaction. The other raw material types, ratios and preparation processes are the same.
[0093] Test Example 1-2:
[0094] Test Example 1: Feasibility Verification Test
[0095] Test method description:
[0096] Test Item 1: Solvent Extraction Stability Test of Surface Lubricating Layer
[0097] Pipe samples prepared in Example 1, Comparative Example 2 (physical addition of dimethyl silicone oil), and Comparative Example 5 (no reactive grafted carrier) were selected. The pipes were cut axially, and strips with a length of 100 mm and a width of 20 mm were cut. First, the initial static friction coefficient of the inner wall of the strip was tested using a friction coefficient meter. Then, the strip was immersed in n-hexane solvent and treated in an ultrasonic cleaner for 15 min to simulate an extreme surface precipitate cleaning process. The strip was then removed and dried in a 60°C oven for 30 min to completely evaporate the solvent. After cooling to room temperature, the static friction coefficient of the inner wall was tested again. The rate of change of friction coefficient before and after solvent extraction was calculated. The smaller the rate of change, the stronger the bond between the lubricating layer and the substrate.
[0098] Test Item 2: Torque Rheological Performance Test. The reactive extrusion process was simulated using a Haake torque rheometer.
[0099] Weigh out 60g of the total dry mix formulations corresponding to Example 1, Comparative Example 3 (without zinc stearate), and Comparative Example 4 (without pre-prepared precursor). Set the rheometer speed to 60rpm and the mixing chamber temperature to 175℃ (simulating the reaction temperature of the compression section). Record the process from the start of material feeding to reaching the equilibrium torque, focusing on the plasticizing time and the equilibrium torque value. Too high an equilibrium torque indicates that the reaction is too fast, leading to crosslinking or viscosity runaway, while too short a plasticizing time indicates that the crosslinking reaction occurs too early.
[0100] Experimental data:
[0101] Table 1. Feasibility Verification Test Data Recording Table
[0102] Example 1 0.174 0.182 +4.6 18.6 145 The machining torque curve is smooth and without fluctuations. Comparative Example 2 0.168 0.385 +129.2 16.2 110 The surface feels rough after extraction, and a large amount of lubricant is lost. Comparative Example 3 0.295 0.301 +2.0 25.4 85 High initial coefficient of friction, excessive torque Comparative Example 4 0.215 0.238 +10.7 21.8 105 There are slight flow marks on the surface. Comparative Example 5 0.185 0.362 +95.7 16.8 115 Similar to Comparative Example 2, without chemical anchoring
[0103] Mechanism Analysis and Conclusions: Based on the test data in Table 1, the following technical conclusions can be drawn:
[0104] Regarding the stability of the surface lubricating layer, after ultrasonic extraction with the strong solvent n-hexane, the static friction coefficient of Example 1 increased by only 4.6%, maintaining excellent lubrication performance. In contrast, the friction coefficients of Comparative Examples 2 and 5 increased by more than 90% after extraction. The results confirm that the terminal amino polysiloxane in Example 1 is not physically attached to the polyvinyl chloride surface in a free state, but forms a stable structure that is resistant to migration and solvents through the chemical bonding of maleic anhydride-grafted polyethylene and the physical anchoring effect of zinc ion clusters. Although Comparative Example 5 contains maleic anhydride-grafted polyethylene, it lacks reactivity (using ordinary polyethylene), which prevents the lubricant from being grafted, thus confirming the necessity of the grafting reaction.
[0105] Regarding the processing rheological behavior, Comparative Example 3, in the absence of zinc stearate coordination, had an equilibrium torque as high as 25.4 N·m and an extremely short plasticizing time (85 s). This indicates that the amino-terminated polysiloxane and maleic anhydride-grafted polyethylene undergo a rapid imidization reaction in the early stage of melting, generating a high-viscosity cross-linked or long-branched structure, which leads to poor flowability. The lubricating components are locked inside the matrix and cannot migrate to the surface (corresponding to an initial friction coefficient as high as 0.295).
[0106] Conversely, Example 1, by introducing an active lubricating precursor and utilizing the coordination effect of zinc stearate and intermediate amic acid, controlled the equilibrium torque at 18.6 N·m and extended the plasticizing time to 145 s. This indicates that the introduction of zinc ions delayed the occurrence of the final ring-closure reaction, preserved the fluidity of the graft during processing, and enabled the modified lubricating component to migrate to the pipe surface and achieve efficient lubrication after cooling. Although Comparative Example 4 added zinc stearate, it did not undergo pre-complexation. Its torque and coefficient of friction were between those of Example 1 and Comparative Example 3, indicating that the pre-complexation process is crucial for forming a uniform coordination intermediate.
[0107] Test Example 2: Performance Indicator Comparison Test
[0108] Test method description:
[0109] The friction coefficient test was conducted in accordance with GB / T10006-2021 "Determination of the coefficient of friction of plastic films and sheets". The pipe was cut open along the axial direction and flattened, and cut into samples of specified size. The static friction coefficient and dynamic friction coefficient between the inner wall of the sample and the standard steel rod were tested at room temperature (23±2℃) with the test speed set to 100mm / min.
[0110] After thermal aging, the friction coefficient test involves placing the cut inner wall sample of the pipe in a forced-air drying oven and continuously heating it at 60°C for 168 hours. After removing the sample and adjusting it for 24 hours in a standard laboratory environment, the dynamic friction coefficient is measured again according to the above friction coefficient test method. The dynamic friction coefficient is used to reflect the migration stability and anti-leakage ability of the lubricating components under heated conditions.
[0111] Tensile property testing was conducted in accordance with GB / T8804.1-2003 "Determination of tensile properties of thermoplastic pipes - Part 1: General test methods". Dumbbell-shaped specimens were punched from the pipe and tested using a universal testing machine. The tensile speed was set to 50 mm / min, and the tensile yield strength and elongation at break were recorded.
[0112] The flattening test was conducted according to the flattening test method in GB / T9647-2015 "Determination of Ring Stiffness of Thermoplastic Pipes". A 50mm long pipe section was cut and a compressive load was applied vertically until the outer diameter of the pipe was deformed to 40% of the outer diameter. The pipe sample was then observed to see if it cracked or delaminated.
[0113] Surface appearance assessment involves visually inspecting the inner and outer surfaces of the pipe under a standard light source and recording any presence of pitting, flow marks, exudates (blooming), or uneven color.
[0114] Experimental data:
[0115] Table 2. Summary of Comprehensive Performance Test Data for Pipes in Each Example and Comparative Example
[0116] Example 1 0.174 0.158 0.163 46.8 142 No cracks Smooth and uniform Example 2 0.162 0.145 0.151 44.2 138 No cracks Smooth, slightly oily Example 3 0.205 0.191 0.194 48.5 126 No cracks Smooth and uniform Example 4 0.181 0.166 0.172 46.1 135 No cracks Smooth and uniform Example 5 0.188 0.174 0.181 45.9 130 No cracks Smooth and uniform Comparative Example 1 0.385 0.342 0.338 51.2 115 No cracks Dry, dull Comparative Example 2 0.165 0.152 0.285 39.4 85 Microcracks appeared The surface is oily and has precipitates. Comparative Example 3 0.315 0.298 0.295 47.6 108 No cracks The surface is rough and has flow marks. Comparative Example 4 0.235 0.218 0.242 45.3 120 No cracks There are pockmarks in some areas. Comparative Example 5 0.178 0.165 0.310 41.5 92 Cracking at the edge of the sample The surface turns white after being placed.
[0117] Results Analysis and Conclusions: Based on the test data in Table 2, the technical solution proposed in this invention is analyzed as follows:
[0118] Friction performance and long-term stability: The pipes of Examples 1 to 5 all showed significantly better low friction characteristics than Comparative Example 1 (blank control). The dynamic friction coefficient was mainly distributed in the range of 0.145 to 0.191. In particular, after 168 hours of thermal aging at 60°C, the dynamic friction coefficient of Example 1 only increased slightly from 0.158 to 0.163, indicating that the lubrication layer was stable.
[0119] Conversely, although Comparative Example 2 (direct addition of dimethyl silicone oil) had a low initial coefficient of friction (0.152), it rapidly increased to 0.285 after thermal aging. This confirms that the free small molecule silicone oil migrated and evaporated after heating. Comparative Example 5 (non-reactive grafting) showed a similar trend, with the coefficient of friction deteriorating after aging. This indicates that a physical blend system lacking chemical bonding cannot meet the requirements for long-term communication tubing.
[0120] Reaction Delay and Surface Enrichment Mechanism: Comparative Example 3 (without zinc stearate) had a friction coefficient as high as 0.298, far higher than Example 1, despite the addition of reactive raw materials. This confirms that in the absence of zinc ion coordination protection, the terminal amino polysiloxane and maleic anhydride grafted polyethylene completed the imidization ring-closure reaction prematurely inside the extruder. The viscosity of the resulting macromolecular product increased sharply, and it lost its ability to migrate to the surface. As a result, most of the lubricant was buried in the core layer of the pipe and failed to play a surface lubrication role.
[0121] The coefficient of friction of Comparative Example 4 (without pre-prepared precursor) was 0.218, which was between that of Example 1 and Comparative Example 3, and local pitting appeared on the surface. This indicates that if zinc ions are not pre-positioned around the amino group through a pre-prepared precursor process, the coordination efficiency of zinc ions will be reduced, leading to partial runaway reaction and decreased dispersion uniformity.
[0122] Maintaining mechanical properties: Adding liquid lubricant will cause the mechanical properties of polyvinyl chloride to decrease. As shown in Comparative Example 2, its tensile yield strength drops to 39.4 MPa and its elongation at break is only 85%. Microcracks also appear in the flat test. This is because the free silicone oil destroys the interaction forces between the polyvinyl chloride molecular chains.
[0123] In Example 1, while achieving low friction, the tensile yield strength remained at 46.8 MPa, and the elongation at break was increased to 142% (superior to 115% of Comparative Example 1). This is because the generated maleic anhydride-grafted polyethylene-grafted polydimethylsiloxane copolymer not only played a lubricating role, but the polyethylene backbone also played a toughening effect similar to that of an elastomer. Furthermore, the grafting structure improved the interfacial compatibility between the lubricating phase and the polyvinyl chloride body, eliminating microscopic defects.
[0124] In summary, this invention solves the problems of lubricant precipitation, difficult migration of reactive lubricants, and loss of mechanical properties in traditional technologies by using zinc ion coordination-induced delayed reaction and thermally reversible anchoring mechanism.
Claims
1. A PVC conduit for communication cabling, characterized in that, By weight, it consists of the following components: Polyvinyl chloride resin 90.0-110.0 parts; calcium-zinc composite heat stabilizer 3.5-4.5 parts; stearic acid 0.3-0.4 parts; polyethylene wax 0.4-0.5 parts; maleic anhydride grafted polyethylene 3.0-5.0 parts; acrylate processing aids 1.0-2.0 parts; nano calcium carbonate 10.0-15.0 parts; active lubricant precursor 1.4-2.8 parts; The active lubricating precursor is a mixture obtained by swelling and compounding amino-terminated polysiloxane and zinc stearate under heating conditions; The weight ratio of the amino-terminated polysiloxane to the zinc stearate is (2.0-3.0):1; The amino value of the terminal amino polysiloxane is 0.3 mmol / g-0.6 mmol / g, and the viscosity of the terminal amino polysiloxane at 25°C is 1000 mPa·s-5000 mPa·s. The nano-calcium carbonate has a particle size of 40nm-80nm; the maleic anhydride grafting rate in the maleic anhydride-grafted polyethylene is 0.8%-1.2%; The active lubricating precursor is obtained by heating and stirring terminal amino polysiloxane and zinc stearate at 110-120°C for 20-30 minutes, causing zinc stearate to swell and combine in the terminal amino polysiloxane, and then naturally cooling to 50-60°C after stopping heating.
2. A method for preparing a PVC conduit for communication cabling as described in claim 1, characterized in that, Includes the following steps: S1. Preparation of active lubricating precursor: Amin-terminated polysiloxane is mixed with zinc stearate, and the zinc stearate is swollen in the amin-terminated polysiloxane under heating and stirring conditions. After cooling, the active lubricating precursor is obtained. S2. High-speed mixing: Polyvinyl chloride resin, calcium-zinc composite heat stabilizer, stearic acid and polyethylene wax are put into a high-speed mixer for initial mixing; after heating, maleic anhydride grafted polyethylene, acrylate processing aids and nano calcium carbonate are added; when the temperature is further increased to a specific temperature range, the active lubricating precursor is added; after high-speed stirring, the material is discharged. S3, Cooling and Mixing: The material obtained in step S2 is cooled in a cold mixer and allowed to stand and mature to obtain a dry PVC mixture; S4. Reactive extrusion molding: The PVC dry mixture is added to an extruder, and after plasticizing extrusion, shaping, cooling and cutting, the PVC pipe for communication cabling is obtained.
3. The method for preparing a PVC conduit for communication cabling according to claim 2, characterized in that, The specific operation of step S2 is as follows: The polyvinyl chloride resin, the calcium-zinc composite heat stabilizer, the stearic acid, and the polyethylene wax are added to a high-speed mixer at a speed of 450 rpm-550 rpm. High-speed mixing is initiated to utilize frictional heat for heating. When the material temperature reaches 80℃-85℃, the maleic anhydride-grafted polyethylene, the acrylate processing aid, and the nano-calcium carbonate are added. Continue stirring at high speed. When the material temperature rises to 112℃-115℃, add the active lubricating precursor. Continue stirring at high speed for 120-150 seconds. When the material temperature reaches 120℃-125℃, discharge the material into the cold mixer.
4. The method for preparing a PVC conduit for communication cabling according to claim 2, characterized in that, In step S3, the cooling temperature in the cold mixer is 40℃-45℃, and the settling and ripening time is 12h-24h.
5. The method for preparing a PVC conduit for communication cabling according to claim 2, characterized in that, In step S4, the extruder is a conical twin-screw extruder, and the temperature settings for each zone of the conical twin-screw extruder are as follows: the feeding section temperature is 150℃-160℃; the compression section temperature is 165℃-175℃; the metering section temperature is 175℃-185℃; the confluence core temperature is 175℃-180℃; and the die temperature is 185℃-190℃.
6. The method for preparing a PVC conduit for communication cabling according to claim 5, characterized in that, In step S4, the main screw speed of the conical twin-screw extruder is 18 rpm-25 rpm, and the feeding speed is 20 rpm-28 rpm.
Citation Information
Patent Citations
Environment-friendly PVC (polyvinyl chloride) solid-wall pipe for underground communication pipelines
CN107266814A
Thermoplastic flame-retardant bio-based PA56-PA66 composite material and preparation method thereof
CN109957238A
Anti-damage low-temperature-resistant cable material
CN110684304A